Community Radio: a critical analysis of the relationship between funding sources, programming and developmental role - Sithole, Enoch (My University, 2020)
The normative function of community radio is to, inter alia, play a developmental role in the community it serves. Playing a developmental role is among the key distinctions between community radio and its public and commercial counterparts. The medium is expected to respond to the needs of the community it serves, rather than the demands of its funders or any other interests. However, the challenge to be financially sustainable has forced community radio to gravitate towards responding to the needs of funding sources, be they commercial, in the form of advertising and sponsorship, NGO donors or government institutions. This has led to several accusations being levelled against the sector: community radio is operating in the same space as its public and commercial counterparts; its programming and editorial content are influenced by funding sources; it’s commercial radio in disguise; and most importantly, it no longer plays its community development role. This study critical analysis the relationship between funding sources, programming and editorial content and the developmental role of community radio. The research reveals a sector in serious financial distress. In some cases, at least, funding sources play a critical role in programming and editorial content choices of community radio stations. This has, indeed, posed serious challenges to the stations’ ability to pursue their developmental role. The research revealed the need for urgent interventions to return community radio to its normative role
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, in fulfilment of the Degree of Master of Arts in Journalism and Media Studies, 2020
Keywords: Radio broadcasting--South Africa; Community radio--South Africa; Radio programs--Planning